Prospects for using plant-based biomass in the construction of bio-based houses - Pancaldi, Francesco; van den Oever, Martien; van der Weide, Rommie; van Baren, Sven; Abdulbawab, Sanabel; van Rooij, Sabine; van Buuren, Michael; van der Voort, Marcel; van Kampen, Arjen; Trindade, Luisa M. (Frontiers in Plant Science, 2025)
The construction industry is a major contributor to climate change, due to the extensive use of non-renewable materials, such as concrete and steel. Bio-based materials manufactured from diverse plant biomass sources – mainly wood, lignocellulosic biomass, and plant fibres – offer sustainable alternatives, potentially transforming buildings into net carbon sinks. However, the establishment of effective value chains for the provision and deployment of biomass in “largely bio-based” houses (i.e. houses with main elements made up of bio-based materials) is still far from being reached. This depends largely on the level of optimisation of bio-based vs conventional construction materials. In this context, this opinion paper explores the feasibility of building “largely bio-based” houses by discussing both the availability and the diverse functional roles that different biomass types from diverse plant species can have in construction applications. Moreover, the article highlights current research challenges in the supply of high-quality biomass for “bio-based houses”. Finally, it discusses how the effective integration of plant science, material engineering, as well as environmental and economic research in trans-disciplinary research efforts is key to set up operational and self-standing bio-based construction value chains.